PTBP3 Induced Inhibition of Differentiation of Gastric Cancer Cells Through Alternative Splicing of Id1 - Chen, Bin; Chen, Weixia; Mu, Xiaoyan; Yang, Liyan; Gu, Xiangyu; Zhao, Aiguang; Liang, Xin; Liu, Jianwen (Frontiers in Oncology, 2020)
Overexpression of PTBP3, a factor involved in alternative splicing, may inhibit the differentiation of leukemia cells. However, its role in gastric cancer differentiation and the specific pathways involved are unclear. In this study, we found that PTBP3 was upregulated in the poorly differentiated gastric cancer tissues. Patients with high levels of PTBP3 expression had significantly shorter survival than those with low PTBP3 expression. In gastric cancer cells, the regulatory effect of PTBP3 on alternative splicing of the Id1 gene was investigated. Following sodium butyrate-induced differentiation of MKN45 cells, the expression of Id1a decreased, but the expression of Id1b increased. RNA interference and overexpression experiments showed that PTBP3 upregulated Id1a expression and downregulated Id1b expression. RNA immunoprecipitation (RIP) assays indicated PTBP3 could interact with Id1. UV cross-linking assays indicated that PTBP3 interacted with the CU rich region of the Id1 gene. Two-hybrid experiments and a gel mobility shift assays found that Id1b had a more potent affinity for Hes1 than Id1a. Chromatin immunoprecipitation (ChIP) assays verified the association of Hes1 and the promoter of PTBP3 gene. Luciferase assays revealed that Hes1 bound the N-box sequence in the PTBP3 promoter. After silencing or overexpression of Hes1, PTBP3 protein expression remained unchanged. Thus, the loss of feedback regulation among PTBP3, Id1, and Hes1 in gastric cancer cells may be one of the causes of inhibited differentiation and malignant proliferation of these cells.